تعليم مهارة الاستماع الفعال وكيفية اختبارها فى اللغة العربية - Faisal Faisal (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2023)
مستخلص البحثمهارة الاستماع هي أولى المهارات التي يمر بها الطفل في اكتساب لغته الأم. ومن المعلوم أن من لم يسمع لايتكلم. لذا، هذه المهارة لها دور مهم في حياة الأفراد. يهدف هذا البحث لعرض تعليم مهارة الاستماع وكيفية اختبارها في اللغة العربية. هذه الدراسة هي دراسة وصفية واكتشافية في تعليم مهارة الاستماع واختبارها في اللغة العربية.ونتيجة هذا البحث أن مهارة الاستماع هي تكرار الأصوات باللغة الجديدة حتى فتقاتده الأذن أي القدرة على سمع الكلمات والجمل والعبارات بسمع سليم من الناطق ويعبرها بمهارة الكلام. أما كيفية اختبارة هذه المهارة هي يمكنه 1) اختبار موضوعي 2) اختبار ذاتي 3) اختبار انتاجي و 4) اختبار تعرفي. وشكل هذا الاختبار منها أ) أن يوجه المعلم لطلابه أسئلة شفهية أو كتابية تتعلق بالنص المحدد، ب) يوجه المعلم لطلابه أسئلة من نوع (الاختيار من متعدد) ويطلب منهم تحديد الإجابة الصحيحة، ج) أن يوجه المعلم لطلابه أسئلة من نوع (صح/خطأ) وفقا لما سمعوه أو شاهدوه أو قرؤوه، د) وأن يوجه المعلم لطلابه أسئلة من نوع (ملء الفراغ ) أن يوجه المعلم لطلابه أسئلة من نوع (المزاوجة) ه) أن يوجه المعلم لطلابه أسئلة من نوع (الترتيب) و) أن يطلب المعلم من طلابه تلخيص ما سمعوه موضحين الأفكار الأساسية.الكلمات الأساسية: تعليم، مهارة الاستماع، اختبارات.Abstract Listening skill is the first skill that a child passes through in acquiring his mother tongue. It is well known that he who does not hear does not speak. So, this skill has an important role in people's lives. The aim of this research is to present the teaching of listening skill and how to test it in the Arabic language. This study is a descriptive and exploratory study in teaching and testing the listening skill in the Arabic language. The result of this research is that the skill of listening is the repetition of sounds in the new language until the ear leads him, that is, the ability to hear words, sentences and phrases with sound hearing from the speaker and express them with speaking skill. As for how to test this skill, it can: 1) an objective test 2) a subjective test 3) a productivity test and 4) a cognitive test. This test consisted of: a) for the teacher to ask his students oral or written questions related to the selected text, b) for the teacher to ask his students questions of the type (multiple choice) and ask them to select the correct answer, c) for the teacher to ask his students questions of the type (true/false). d) According to what they have heard, seen or read, d) The teacher asks his students questions of the type (fill in the blank) The teacher asks his students questions of the type (pairing) e) That the teacher asks his students questions of the type (arrangement) f) That the teacher asks His students summarize what they heard explaining the main ideas.Keywords: Education, Listening skill, Tests